Implementation Of Integrated Quality (Mmt) In Improving The Quality Of Open High School Graduates - Wardhana, Nanang; Wasliman, Iim; Warta, Waska; Cepi Barlian, Ujang (CV. Inara, 2022)
The number of limitations/obstacles experienced by some graduates of SMP/MTs who cannot continue their education to a higher level, namely High School/SMK/MA due to several limitations, among others: due to financial factors of parents, children as the backbone of the family, geographical conditions experienced by some participants students to regularly come every day to a regular high school, as well as the difficulty of public transportation as access to school.The purpose of this research is to find out how the implementation of Integrated Quality Management (MMT) in improving the quality of graduates of SMA Open actually through the management theory approach